The Role of the Chloroplast in the Replication of Positive-Sense Single-Stranded Plant RNA Viruses - Budziszewska, Marta; Obrępalska-Stęplowska, Aleksandra (Frontiers in Plant Science, 2018)
Positive-sense single-stranded plant RNA viruses are obligate intracellular parasites that infect many agriculturally important crops. Most known plant RNA viruses are characterized by small genomes encoding a limited number of multifunctional viral proteins. Viral pathogens are considered to be absolutely dependent on their hosts, and viruses must recruit numerous host proteins and other factors for genomic RNA replication. Overall, the replication process depends on virus–plant protein-protein, RNA–protein and protein–lipid interactions. Recent publications provide strong evidence for the important role of chloroplasts in viral RNA synthesis. The chloroplast is considered to be a multifunctional organelle responsible for photosynthesis and for the generation of plant defense signaling molecules. High-throughput technologies (genomics and proteomics), and electron microscopy, including three-dimensional tomography, have revealed that several groups of plant RNA viruses utilize chloroplast membranes to assemble viral replication complexes (VRCs). Moreover, some chloroplast-related proteins reportedly interact with both viral proteins and their genomic RNAs and participate in trafficking these molecules to the chloroplast, where replication occurs. Here, we present the current knowledge on the important role of chloroplasts in the viral replication process.